Genome-Based Characterization of Biological Processes That Differentiate Closely Related Bacteria - Palmer, Marike; Steenkamp, Emma T.; Coetzee, Martin P. A.; Blom, Jochen; Venter, Stephanus N. (Frontiers in Microbiology, 2018)
Bacteriologists have strived toward attaining a natural classification system based on evolutionary relationships for nearly 100 years. In the early 20th century it was accepted that a phylogeny-based system would be the most appropriate, but in the absence of molecular data, this approach proved exceedingly difficult. Subsequent technical advances and the increasing availability of genome sequencing have allowed for the generation of robust phylogenies at all taxonomic levels. In this study, we explored the possibility of linking biological characters to higher-level taxonomic groups in bacteria by making use of whole genome sequence information. For this purpose, we specifically targeted the genus Pantoea and its four main lineages. The shared gene sets were determined for Pantoea, the four lineages within the genus, as well as its sister-genus Tatumella. This was followed by functional characterization of the gene sets using the Kyoto Encyclopedia of Genes and Genomes (KEGG) database. In comparison to Tatumella, various traits involved in nutrient cycling were identified within Pantoea, providing evidence for increased efficacy in recycling of metabolites within the genus. Additionally, a number of traits associated with pathogenicity were identified within species often associated with opportunistic infections, with some support for adaptation toward overcoming host defenses. Some traits were also only conserved within specific lineages, potentially acquired in an ancestor to the lineage and subsequently maintained. It was also observed that the species isolated from the most diverse sources were generally the most versatile in their carbon metabolism. By investigating evolution, based on the more variable genomic regions, it may be possible to detect biologically relevant differences associated with the course of evolution and speciation.